Hubungan Jumlah Bakteri Patogen dalam Rumah dengan Kejadian Pneumonia pada Balita di Wilayah Kerja Puskesmas Ngesrep Banyumanik Semarang Tahun 2014 - Caesar, David Laksamana; Nurjazuli, Nurjazuli; Wahyuningsih, Nur Endah (Jurnal Kesehatan Lingkungan Indonesia, 2015)
Background : Pneumonia is an acute respiratory tract infections, in which there is inflammation in the lung tissue, caused by microorganisms such as viruses, bacteria, fungi, inhaled foreign particles or irradiation. Semarang is a city with a high incidence of pneumonia, subdistrict Banyumanik is a district with a high incidence rate is 103.25 per 1000 population in 2012. Methods : This is an observasional reseach using case control design. The population in this research is 162 children under five years, using Random Sampling techniques, a sample of 70 children under five years.The data collection method in this research is the measurement by using the colony counter, lux metter, thermohygrometer, observations, questionnaires, interviews, and documentation. And data analysis in this study using chi square test and logistic regression test. Results : The results showed there was no significant relationship between the amount of bacterial pathogen in the house with incidence of pneumonia onchildren under five years with p value (0.356); OR (4.387); CI 95% (0.465-41.404) for Staphilococcus aureus, p value (0.112); OR (2.364), CI 95% (0.807-6.927) for Klebsiella pneumoniae, and p value (0.473); OR (1.410); CI 95% (0.551) for Pseudomonas aeruginosa. No significant relationship between temperature, lighting, and ventilation with the incidence of pneumonia on children under five years with p value (0.101);OR (2.522);CI 95% (0.821-7.748), p (0.614); OR (3.188); CI 95% (0.315-32.144), p (0.632); OR (0.795); CI 95% (0.311-2.034). Any relationship humidity with pneumonia the incidence of pneumonia on children under five years with p value (0.012); OR (0.265), CI 95% (0.092-0.765). Conslusion : The conclution of this reseach is a significant relationship between humidity with pneumonia on children under five years in working areas Public Health Center Ngesrep Banyumanik Semarang 2014. Keyword : Bacterial Pathogen, Pneumonia for Children Under Five Years, Ngesrep Bayumanik